SOCIALISM IDEOLOGY IN NOVEL O BY EKA KURNIAWAN (Genetics Structuralism Study) - Martini Martini; Zuriyati Zuriyati; Saifur Rohman (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2018)
AbstractThis research points to gain the comprehensive of socialism ideology in novel O by Eka Kurniawan investigated by genetical structuralism. A novel is an interesting literary work contains kinds of topics inside, but there is stil a line or certain contents on it. A social genre novel brings social stories in this research. This research inspects how socialism ideology described in this novel by genetics structuralism. The focus goaled to find out how does socialism ideology describe the existence of humanism fact in novel O based on genetics structuralism. Analytic method used in this research, it observes attentively technic and notes after the writer read and studied the novel many times to gain a better comprehensive. Research result shows that there is socialism ideology based on humanity fact described in novel O written by Eka Kurniawan has seen on a police character that is social classes cover ; lower social class taken by a monkey, a description of lower society beside police as a middle class.Keywords: Socialism Ideology, Novel O, Genetics Structuralism